Controlled Growth-Dependent Electrochemical Behavior of Cobalt and 1,3,5 Benzene-Tricarboxylic Acid-Based Mofs for Efficient Supercapacitor Applications - Serafini, D; Singh, D; Navarrete-Villegas, A; Manquián-Villalobos, C (Elsevier Ltd, 2024)
This study investigates the synthesis and electrochemical performance of cobalt-BTC acid-based metal-organic frameworks (Co-MOFs) under different hydrothermal conditions. The crystal growth was controlled by varying the concentration of NaOH during synthesis, resulting in three Co-BTC MOF varieties (labeled as COMOFDW-0mM, COMOFDW-3mM, and COMOFDW-6mM). Exhaustive structural-microstructural characterizations, including X-ray diffraction (XRD), scanning electron microscopy (SEM), and N2 adsorption-desorption isotherms, elucidate the structural and morphological variation among these Co-BTC MOF varieties. The crystal structures of COMOFDW-0mM and COMOFDW-3mM exhibit similar laminar configurations, while COMOFDW-6mM shows major variations, such as changes in the coordination modes between BTC and cobalt complexes and differences in BTC plane directions in MOF crystal faces. SEM images reveal distinctive needle-like morphologies, and the as-synthesized crystals exhibit varying aspect ratios. Nitrogen adsorption-desorption isotherms indicate variations in the presence of micropores and mesoporosities, revealing microstructural differences. Electrochemical evaluations in a three-electrode system reveal superior performance for COMOFDW-6mM, with a maximum specific capacitance of 261.27 F/g, an energy density of 7.34 Wh/kg, and a maximum power density of 1325.2 W/kg under 2 M KOH electrolyte. Two-electrode coin cell measurements further validate its potential, maintaining competitive capacitance values. This systematic exploration of Co-MOFs not only elucidates the impact of growth conditions on crystal structures but also underscores the potential for tailoring electrochemical properties. Moreover, the findings present opportunities for further enhancements through composite strategies, opening new avenues for advancing MOFs in energy storage applications. © 2024 Elsevier B.V.